Carnivalising Postcolonial Zimbabwe: the Vulgar and Grotesque Logic of Postcolonial Protest in NoViolet Bulawayo's We Need New Names (2013) - Ngoshi, Hazel T. (Taylor & Francis (Routledge), 2016)
This article set out to explore NoViolet Bulawayo’s We need new names from the perspective of carnivalised writing. The objectives of the article were to unpack how the vulgar and the grotesque were used to create carnival moments in the narrative and to examine how marginal subjects gain voice and some degree of power to live an alternative life, even if this is momentary. It sought to examine how Bulawayo derives her aesthetics from the vulgar and the grotesque to create a carnivalesque logic that informs postcolonial protest in the novel. The analysis made use of the theoretical concepts of carnival propounded by Mikhail Bakhtin. This article argues that the text is constituted by a regime of the vulgar, which the child characters deploy for transgressing hegemonic practices and authoritative discourses. Social norms are suspended and the children have a subversive agency, courtesy of parody and satire. The article reveals that apart from speaking back to power, the children harness the image of kaka (human excrement) as a discursive resource to satirise the failures of the Zimbabwean postcolony and to degrade all forms of authority. It is concluded that while the scatological in the novel suggests social indictment, the images of kaka and dirt fail to transcend protest to see the realisation of a desired postcolonial condition.